Nonlinear optics with coherent free electron lasers. (5th August 2016) - Bencivenga, F; Capotondi, F; Mincigrucci, R; Cucini, R; Manfredda, M; Pedersoli, E; Principi, E; Simoncig, A; Masciovecchio, C
Abstract: We interpreted the recent construction of free electron laser (FELs) facilities worldwide as an unprecedented opportunity to bring concepts and methods from the scientific community working with optical lasers into the domain of x-ray science. This motivated our efforts towards the realization of FEL-based wave-mixing applications. In this article we present new extreme ultraviolet transient grating (X-TG) data from vitreous SiO2, collected using two crossed FEL pulses (photon frequency 38 eV) to generate the X-TG and a phase matched optical probing pulse (photon frequency 3.1 eV). This experiment extends our previous investigation, which was carried out on a nominally identical sample using a different FEL photon frequency (45 eV) to excite the X-TG. The present data are featured by a peak intensity of the X-TG signal substantially larger than that previously reported and by slower modulations of the X-TG signal at positive delays. These differences could be ascribed to the different FEL photon energy used in the two experiments or to differences in the sample properties. A systematic X-TG study on the same sample as a function of the FEL wavelength is needed to draw a consistent conclusion. We also discuss how the advances in the performance of the FELs, in terms of generation of fully coherent photon pulses and multi-color FEL emission, may push the development of original experimental strategies to study matter at the femtosecond–nanometer time–length scales, with the unique option of element and chemical state specificity. This would allow the development of advanced experimental tools based on wave-mixing processes, which may have a tremendous impact in the study of a large array of phenomena, ranging from nano-dynamics in complex materials to charge and energy transfer processes.